2016
DOI: 10.1523/jneurosci.3709-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Glaucomatous Neurodegeneration by Differentially Modulating Neuronal Endoplasmic Reticulum Stress Molecules

Abstract: Axon injury is an early event in neurodegenerative diseases that often leads to retrograde neuronal cell death and progressive permanent loss of vital neuronal functions. The connection of these two obviously sequential degenerative events, however, is elusive. Deciphering the upstream signals that trigger the neurodegeneration cascades in both neuronal soma and axon would be a key step toward developing the effective neuroprotectants that are greatly needed in the clinic. We showed previously that optic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 67 publications
3
79
1
1
Order By: Relevance
“…We previously showed that ER stress is induced by ON injury and that CHOP deletion in combination with XBP-1s overexpression synergistically promotes neuroprotection of RGC somata and axons in mouse ON crush model, microbead-induced glaucoma model and EAE/optic neuritis(29, 34, 35). These results suggested that these ER stress molecules are potential therapeutic targets for neuroprotection in optic neuropathies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that ER stress is induced by ON injury and that CHOP deletion in combination with XBP-1s overexpression synergistically promotes neuroprotection of RGC somata and axons in mouse ON crush model, microbead-induced glaucoma model and EAE/optic neuritis(29, 34, 35). These results suggested that these ER stress molecules are potential therapeutic targets for neuroprotection in optic neuropathies.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined whether the SOHU model can be used to evaluate the effect of ER stress manipulation on glaucomatous RGCs and ON. We previously demonstrated that the microRNA-based AAV-CHOP shRNA-GFP knocks down endogenous CHOP in mouse retinas and increases RGC soma and axon survival in the ON crush model and microbeads-induced glaucoma model(29). We modified this AAV vector by replacing GFP with XBP-1s to knockdown CHOP and express XBP-1s with a single AAV vector.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MYOC mutations reportedly affect the ER stress response, which has been implicated in the pathogenesis of glaucoma (Chrysostomou et al, 2013; Zode et al, 2012; Zode et al, 2011). ER stress pathways also appear to play a role in the pathogenesis of POAG in the retina based on mouse models of optic nerve injury or transgenic mutated myocilin (Carbone et al, 2011; Hu et al, 2012; Yang et al, 2016a; Zode et al, 2012; Zode et al, 2011). Mitochondrial-related pathways have also been implicated in POAG pathogenesis.…”
Section: Association Studies In Poagmentioning
confidence: 99%